2019
DOI: 10.2147/ijn.s211898
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Nanofibrous vildagliptin-eluting stents enhance re-endothelialization and reduce neointimal formation in diabetes: in vitro and in vivo</p>

Abstract: BackgroundThe high lifetime risk of vascular disease is one of the important issues that plague patients with diabetes mellitus. Systemic oral vildagliptin administration favors endothelial recovery and inhibits smooth muscle cell (SMC) proliferation. However, the localized release of vildagliptin in the diabetic vessel damage has seldom been investigated.Research design and methodsIn this work, nanofiber-eluting stents that loaded with vildagliptin, a dipeptidyl peptidase-4 enzyme (DPP-4) inhibitor, was fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
12
1
Order By: Relevance
“…Thus, a patient-specific stent manufacturing system should be designed for more successful stent therapy. In the [ 161 ] study, a 3D-printed PLA biodegradable polymeric stent was prepared using polydopamine (PDA), polyethyleneimine (PEI), and heparin (Hep) chemistry to prevent restenosis and thrombosis with anticoagulation and excellent blood compatibility. The physicochemical characterization indicated that pristine PLA substrates were well-modified, as the abundant amine surface allowed for coating with a large amount of heparin.…”
Section: New Stent Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, a patient-specific stent manufacturing system should be designed for more successful stent therapy. In the [ 161 ] study, a 3D-printed PLA biodegradable polymeric stent was prepared using polydopamine (PDA), polyethyleneimine (PEI), and heparin (Hep) chemistry to prevent restenosis and thrombosis with anticoagulation and excellent blood compatibility. The physicochemical characterization indicated that pristine PLA substrates were well-modified, as the abundant amine surface allowed for coating with a large amount of heparin.…”
Section: New Stent Systemsmentioning
confidence: 99%
“…However, the localized release of vildagliptin in diabetic vessel damage has seldom been investigated. In the study [ 161 ], sufficient vildagliptin concentrations were delivered for more than 28 days from the nanofibrous membrane coatings on the surfaces of the stents in vitro and in vivo. It was shown that the vildagliptin-eluting PLGA membranes greatly accelerated the recovery of diabetic endothelial and reduced SMC hyperplasia.…”
Section: New Stent Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, considering the close relationship between diabetes and periodontal disease, diabetes drugs such as vildagliptin 148 or insulin 62 loaded membranes might be effective in periodontal defects. Similarly, metformin was loaded on electrospun nanofibrous recently and fabricated functional GBR membranes successfully.…”
Section: Other Drugsmentioning
confidence: 99%
“…This stent accelerated the revival of diabetic endothelia and also decreased neointimal hyperplasia and type I collagen content in the vascular intima than that of the non-vildagliptin-eluting group. 207 Poly-L-lactide films cut and rolled into a cable-tie type stent were coated with rapamycin-eluting biodegradable nanofibers, which exhibited excellent mechanical properties and delivered high drug concentrations for over 4 weeks. Moreover, these stents showed a substantial reduction in intimal hyperplasia in denuded rabbit arteries during 6 months follow-up.…”
Section: Introductionmentioning
confidence: 99%